TRUST AND WORK SATISFACTION AFFECTING TEACHERS’ CITIZENSHIP BEHAVIOR - Syafa'at Ariful Huda; Totok Amin Soefijanto; Yetti Supriyati (Erudio Journal of Educational Innovation, 2019)
This study analyzes the influence of organizational justice, trust, and job satisfaction channeled to an organization thoroughly on OCB, and examine and elaborate on the influence of organizational justice and trust on OCB mediated by job satisfaction. The instrument used questionnaires. The samples were determined by the proportional stratified random sampling. From 273 samples of teachers from 305 Private Middle schools in Tangerang Regency, the data analysis used Structural Equation Modeling (SEM).The findings indicated that organizational justice, trust, and job satisfaction significantly influence OCB and organizational justice significantly influenced trust and job satisfaction. The findings prove that job satisfaction and trust of teachers can act as a complete mediation between organizational justice and OCB. The practical implication of this study is to provide knowledge and information for teachers and school management to improve OCB by implementing the concept of organizational justice, trust, and job satisfaction of the teachers.